AUDITOR INDEPENDEN DAN KUALITAS AUDIT : SUATU STUDI EMPIRIS PADA AUDITOR DI KAP JAWA TIMUR - Deddy Kurniawansyah (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2017)
The purpose for this research is to test knowledge,number’s client, peer review to audit quality auditors working in KAP East Java. In this research, we use profesionalisme as Control variable. This study population was auditor’s working in KAP East Java of 610 independent auditor. The sampling used in this study purposive sampling method. Source of data is primary data, obtained from distributed questionares directly and email to auditors working in KAP East Java. This study used multiple regretion analysis to analysis data with the help of the program SPSS 22 edition. The results obtained in this study knowledge, number’s client, and peer review has a positive effect on audit quality auditors working in KAP East Java. For control variable, the results obtained is Profesionalisme has a positive effect on audit quality auditors working in KAP East Java. The results of this study are expected to increase the trust of stakeholders to independent auditors on the quality of the audit. High audit quality reduce asymmetric information and information of the financial statement becomes more relevant and reliable as a basis for decision making.Keyword : Knowladge, Number’s Clients, Peer Review, Audit Quality